Implementation of a quality improvement project on smoking cessation reduces smoking in a high risk trauma patient population. Issue 1 (December 2016) - Nahmias, Jeffry; Doben, Andrew; Poola, Shiva; Korntner, Samuel; Carrens, Karen; Gross, Ronald
Abstract Background Cigarette smoking causes about one of every five deaths in the U.S. each year. In 2013 the prevalence of smoking in our institution's trauma population was 26.7 %, well above the national adult average of 18.1 % according to the CDC website. As a quality improvement project we implemented a multimodality smoking cessation program in a high-risk trauma population. Methods All smokers with independent mental capacity admitted to our level I trauma center from 6/1/2014 until 3/31/2015 were counseled by a physician on the benefits of smoking cessation. Those who wished to quit smoking were given further counseling by a pulmonary rehabilitation nurse and offered nicotine replacement therapy (e.g. nicotine patch). A planned 30 day or later follow-up was performed to ascertain the primary endpoint of the total number of patients who quit smoking, with a secondary endpoint of reduction in the frequency of smoking, defined as at least a half pack per day reduction from their pre-intervention state. Results During the 9 month study period, 1066 trauma patients were admitted with 241 (22.6 %) identified as smokers. A total of 31 patients with a mean Injury Severity Score (ISS) of 14.2 (range 1–38), mean age of 47.6 (21–71) and mean years of smoking of 27.1 (2–55), wished to stop smoking. Seven of the 31 patients, (22.5 %, 95 % confidence interval [CI] of 10–41 %) achieved self-reported smoking cessation at or beyond 30 days post discharge. An additional eight patients (25.8 %, 95 % CI 12–45 %) reported significant reduction in smoking. Conclusions Trauma patients represent a high risk smoking population. The implementation of a smoking cessation program led to a smoking cessation rate of 22.5 % and smoking reduction in 25.8 % of all identified smokers who participated in the program. This is a relatively simple, inexpensive intervention with potentially far reaching and beneficial long-term health implications. A larger, multi-center prospective study appears warranted. LEVEL OF EVIDENCE: Therapeutic Study, Level V evidence.